Relationship Host Behavior and The Environment of DHF Incidence in Wonokusumo Surabaya - Sofa Nutrima Rismawati; Ira Nurmala (Jurnal Berkala Epidemiologi, 2017)
The Free Larvae Index in the 15th Sub-Village Wonokusumo Village is 85%. The incidence of Dengue Hemorrhagic Fever (DHF) in this Sub-Village is still high, 17 cases. The number of DHF incidents is still high due to interactions between host, agent, and environment. Host in terms of behavior, dengue virus as an agent, and the environment come from the surrounding conditions that can cause and trigger the spread of DHF. This study aims to analyze the relationship between host behavior and the environment with the incidence of DHF in the 15th Sub-Village, Wonokusumo, Surabaya. This study uses a cross-sectional design. Random sampling using the guy method. How to calculate the guy method is 10% of the population so that a sample of 78 respondents is obtained. Primary data collection techniques are done through in-depth interviews and questionnaires. Secondary data collection was obtained from the Public Health Center of Wonokusumo and Surabaya City Health Office's report. The study was conducted at the 15th Sub-Village. The results of bivariate statistical tests showed that there was a significant relationship between knowledge (p = 0.00), attitude (p = 0.00), actions (0.00), and the environment with the incidence of DHF. The conclusion of this study is there is an interaction between host and environment (p = 0.00) with the incidence of DHF. Suggestions of this research are the procurement of community service programs every month, the independent larva monitoring movement by the community and the Closing, Draining and Burying Object (3M) plus movement every Thursday on Thursday and the procurement of mosquito larvae monitors cadres training on the ways and rules for administering abate powder according to dosage.